Observations on the explanatory act for the redemption of the land tax: shewing in what instances the provisions of the former act have been amendment or explained, and to what particular cases the additional provisions of the explanatory act are applicable (Bunney, Thompson, and Co.)
With: An act (passed 22d December, 1798,) to enlarge the time limited for the redemption of the land tax; and to explain and amend an act, made in the last session of Parliament, [...]. London, Eyre and Strahan, 1798. 23 cm, 66 p. - With index.